An Investigation of the Sustained Component of Nonphotochemical Quenching of Chlorophyll Fluorescence in Isolated Chloroplasts and Leaves of Spinach. - Ruban, A. V. (1995)
The slowly reversible component of nonphotochemical quenching of Chl fluorescence, ql, has been investigated in intact leaves and chloroplasts of spinach (Spinacia oleracea). In leaves, between 50 and 100% of ql (defined as the quenching that remained after at least 10 min of dark adaptation of a previously illuminated leaf) is instantly reversible when leaves were infiltrated with nigericin. Chloroplasts isolated from leaves in which ql had been induced by prior illumination retained the same level of quenching. No pH gradient, as measured by quenching of 9-aminoacridine fluorescence, was present. However, addition of nigericin caused a partial removal of ql, as observed in whole leaves. It is concluded that ql is not related to a persistence of a bulk phase pH gradient in darkness but to a structural change in the thylakoid that can be reversed by addition of nigericin. The relationship between these observations and the hypothesis that nonphotochemical quenching of chlorophyll fluorescence results from protonation of light-harvesting complex of photosystem II components is discussed.